Awareness Level and Self-Efficacy Beliefs of Pre-service Primary School Teachers Regarding Syrian Students’ Education in Turkey - Kubilay, Sevda; Kılıç, Remzi (Asian Journal of Education and Training, 2019)
The aim of this study is to reveal awareness level and self-efficacy beliefs of pre-service primary school teachers about the education of Syrian students in Turkey. In the research, 20 participants were determined on a voluntary basis among the senior students attending education faculty of a state university. The research was conducted with the focus group interview. Findings indicate that the participants are not aware of the current statistics and educational policies about Syrian students. However, they are aware of the problems that may be encountered in multicultural classrooms. As for the attitudes of participants towards Syrian students, it is revealed that some participants have positive attitudes towards Syrian students and emphasize the concepts of empathy and tolerance but some have negative attitudes. The vast majority of the participants do not feel themselves capable of carrying out educational activities in a multicultural environment. Similarly, they think that the faculties of education do not prepare teacher candidates in this respect. Consequently, it is important for pre-service teachers to have positive attitudes towards Syrian students. It is necessary to provide pre-service teachers with necessary pedagogical background to make them feel professionally competent in multicultural settings.